Preliminary Estimate of Coriolis Force of Vapor Flow in Rotating Heat Pipes Based on Analytical Solution - Huanguang Wang; Qi Yu (International Journal of Photoenergy)
In current theory models for rotating heat pipes, the temperature field of the vapor phase is often supposed to be homogenous, and as a result of such simplification, the experiment result of the heat transfer performance for high rotating speed has some discrepancy with that predicted by theory models. In this paper, the analytical solution of the vapor flow in rotating heat pipes was obtained on the hypothesis of potential flow and with the method of variable separation. A specific rotating heat pipe was examined under three kinds of boundary conditions: linear distribution, uniform but asymmetric distribution, and uniform as well as symmetric distribution of heat load. The flow field was calculated, the Coriolis force is estimated, and it is found that (1) for a rotating heat pipe with high speed or large heat load, it is necessary to consider the Coriolis force, as its magnitude can be that of the gravitational acceleration; (2) the maximum Coriolis force is located at the vapor-liquid interface at the evaporator and condenser sections, and the directions in these two sections are opposite; (3) the Coriolis force is closely related with working conditions and working fluids, and it decreased with working temperature and increased with the heat load; and (4) the maximum viscous shear stress is located at the adiabatic section.